Penggunaan Limbah Kulit Melon Sebagai Pengganti Tepung Terigu Pada Pembuatan American Cookies - Wahyu Ratnasari; Atthaya Nadine Aurelia (Departement of Mathematics Education, 2023)
Melon skin is a waste that can be used as food. One of the food products that can use melon peels is cookies. In this study, melon peels were made into flour and used as a substitute for wheat flour in making American cookies. American cookies that have been made in an organoleptic test to the panelists. From the results of the organoleptic test, it can be concluded that the finished product texture of the american cookies is crunchy, the aroma is less savory, the taste is less sweet and the color is blackish. From the results above, several ways are needed so that the aroma, taste and color of the American cookies remain true to the original.